2022
DOI: 10.1021/acscatal.2c00925
|View full text |Cite
|
Sign up to set email alerts
|

Domino Synthesis of Bicyclic 3,5-Anhydro Furanose Mimics Using a Binary Al(III) Complex/Halide Catalyst

Abstract: Structurally diverse heterobicyclic diethers can be conveniently accessed in good yields through a catalytic domino process that is controlled by a versatile binary catalyst comprising an Al­(III) aminotriphenolate complex and a bromide salt. These bicycles, representing non-natural, 3,5-anhydro furanose mimics, are derived from bis-epoxy substrates through a double cyclization pathway that is initiated by the activation of the free alcohol in the precursor compounds. Various mechanistic control experiments, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[20] The densely functionalized allylic alcohol with axial stereogenicity can be easily transformed into a variety of axially stereogenic building blocks that are otherwise difficult to access (Scheme 5c). Directed epoxida-tion ( 13) [21] and dihydroxylation ( 14) [22] enabled introduction of two additional stereogenic centers without touching the aldehyde moiety. Reduction and reductive amination of 6 a provided diol 15 and amino alcohol 16 in high stereoselectivity.…”
Section: E)mentioning
confidence: 99%
“…[20] The densely functionalized allylic alcohol with axial stereogenicity can be easily transformed into a variety of axially stereogenic building blocks that are otherwise difficult to access (Scheme 5c). Directed epoxida-tion ( 13) [21] and dihydroxylation ( 14) [22] enabled introduction of two additional stereogenic centers without touching the aldehyde moiety. Reduction and reductive amination of 6 a provided diol 15 and amino alcohol 16 in high stereoselectivity.…”
Section: E)mentioning
confidence: 99%
“…The development of catalytic domino processes has attracted much attention among the various established approaches. Different metals or combinations including metal/metal, metal/organo, metal/enzyme, and organo/organo catalysts have been exploited for this purpose. However, the reported methods mainly involve the construction of C–heteroatom bonds, and the formation of heteroatom–heteroatom, especially continuous formation of multiple heteroatom–heteroatom bonds, is rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst basic conditions for the degradation of polycarbonates often release the corresponding diol as a byproduct, 14 to the best of our knowledge, the formation of a fused bicyclic oxetane 8a from the decomposition of polycarbonate is a new observation. 21 Recently, both Buchard and Wooley showed that similar types of bicyclic oxetanes can be used to prepare different kinds of polymers including polycarbonates and polyethers, 22 thus providing a potential recycling or repurposing route for 8a .…”
mentioning
confidence: 99%